Genetic Diversity and Maternal Phylogenetic Relationships among Populations and Strains of Arabian Show Horses - Mohamed Machmoum; Bouabid Badaoui; Daniel Petit; Agnès Germot; Moulay Abdelaziz El Alaoui; Ismaïl Boujenane; Mohammed Piro (Animals, 2023)
Genetic diversity and phylogenetic relationships within the Arabian show horse populations are of particular interest to breeders worldwide. Using the complete mitochondrial DNA D-loop sequence (916 pb), this study aimed (i) to understand the genetic relationship between three populations, the Desert-Bred (DB), a subset of the Kingdom of Saudi Arabia (KSA), United Arab Emirates (UAE) and Bahrain (BAH), the Straight Egyptian (EG) and the Polish bloodline (PL), and (ii) to assess the accuracy of the traditional strain classification system based on maternal lines, as stated by the Bedouin culture. To that end, we collected 211 hair samples from stud farms renowned for breeding Arabian show horses from Nejd KSA, Bahrain, Egypt, Qatar, Morocco, UAE, and Poland. The phylogenetic and network analyses of the whole mitochondrial DNA D-loop sequence highlighted a great genetic diversity among the Arabian horse populations, in which about 75% of variance was assigned to populations and 25% to strains. The discriminant analysis of principal components illustrated a relative distinction between those populations. A clear subdivision between traditional strains was found in PL, in contrast to the situation of DB and EG populations. However, several Polish horse individuals could not be traced back to the Bedouin tribes by historical documentation and were shown to differ genetically from other studied Bedouin strains, hence motivating extended investigations.